Bacterial colonization of explanted non-endocarditis cardiac valves: evidence and characterization of the valvular microbiome. (22nd November 2020) - Di Bella, Stefano; Campisciano, Giuseppina; Luzzati, Roberto; Di Domenico, Enea Gino; Lovecchio, Antonio; Pappalardo, Aniello; Comar, Manola; Gatti, Giuseppe
Abstract: Bacterial colonization has been already demonstrated in heart valve tissues of patients without cardiovascular infections. However, the evidence of a valvular microbiome is still scarce. The next-generation sequencing method was carried out on 34 specimens of aortic ( n = 20) and mitral valves ( n = 14) explanted from 34 patients having neither evidence nor history of infectious diseases, particularly infective endocarditis. While no bacteria were demonstrated using standard culture methods, bacterial deoxyribonucleic acid (DNA) sequences were found using next-generation sequencing in 15/34 (44%) cases. Escherichia coli was present in 6 specimens and was the most frequently identified bacterium. There was a trend towards a higher rate of bacterial DNA positivity in specimens of calcific valves than in those of non-calcific valves (10/17 vs 5/17, P = 0.17). Based on a quantitative test, E. coli accounted for 0.7% ± 1% in calcific valvular tissue and 0.3% ± 0.3% in non-calcific valvular tissue ( P = 0.2), and for 11% ± 27% in the valvular tissue of diabetic patients and 0.3% ± 1% in the valvular tissue of non-diabetic patients ( P = 0.08). Detection of bacterial DNA in non-endocarditis valvular tissues could be a relatively common finding. There could be an association between the valvular microbiome and certain models of valve degeneration and common metabolic disorders. Abstract : The link between the microbiome and the endothelial injury underlying cardiovascular diseases has been investigated with increasing interest throughout the last 2 decades.